Productivity and economics of rabi sorghum (Sorghum bicolor)-summer vegetables cropping sequences under irrigated conditions - RASKAR, B S; BHOI, P G; SHINDE, S H (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted for three years during winter season (rabi) and summer season of 1995-96 to 1997-98 at Rahuri to study the productivity and profitability of rabi sorghum-summer vegetab les cropping sequences under irrigated conditions, The pooled results revealed that the sorghum [Sorghum bicolor (L.) Moench]-okra [Hibiscus esculentus (L.) Moench] sequence gave the significantly highest sorghum grain equivalent yield (26.09 tonnes/ha) and net monetary returns (Rs 11 0678/ha) followed by sorghum-brinjal (Solanum melongena L.) (20.45 tonnes/ha and Rs 82045/ha). Next in order was sorghum-chilli (Capsicum annuum L.) and lowest in sorghum-cluserbean (Cymopsis tetragonoloba L.). The highest consumptive-use was recorded in sorghum-okra (125 cm) but maximum water-use efficiency of 174 kg/ha-cm was recorded in sorghum-brinjal. The per day productivity (Rs 440/day/ha) and returns per unit of water used (Rs 1 094/ha-cm) and benefit: cost ratio (5,17) was maximum in sorghum-okra sequence. Optimum level of irrigation (at 80 mm and 60 mm cumulative pan evaporation to sorghum and vegetables respectively) recorded higher sorghum grain equivalent yieldÂ and net returns than suboptimum (at 125 mm and 90 mm cumulative pan evaporation to sorghum and vegetables respectively). The per day productivity was 32% higher in optimum irrigation than suboptimum irrigation(Rs 262/day/ha).